Role of Lactate Measurement in Flap Monitoring: An Useful Adjunct - Karan Singh; Sheerin Shah; Rajinder K. Mittal; Ramneesh Garg (Indian Journal of Plastic Surgery)
Background Detection of vascular compromise in flap is often a challenging task for reconstructive surgeons. A timely salvage procedure depends on objectivity and reliability of postoperative flap monitoring. This study determined if flap capillary lactate helps in prediction of flap viability in first 48 postoperative hours of surgery.